The places where community is practiced : how store owners and their businesses build neighborhood social life (2019)
Te idea behind this book has a long history. It was inspired less by my academic work than by my family life and side jobs. It is the result of living in and moving between urban and rural neighborhoods as a child, teenager, and student. Growing up in the 1980s, my family lived in inner-city Munich; like most families there, we lived in a small apartment. Gentrifcation has a much longer history in Munich than in Berlin. Our neighborhood began experiencing gentrifcation in the early 1980s, and it is now one of the most expensive areas in Munich. Te lack of space is one reason why we, like many people in Munich, spent a lot of time in beer gardens. Tere, my parents, my younger sister, and I made many friends. We would meet old friends and make new ones, drinking and eating along the common tables or playing at the beer gardens’ playgrounds in the afernoons and evenings. When my mother became pregnant with my second sister and we couldn’t fnd a larger and afordable apartment in the city, my family moved to a smaller town outside of Munich. Tere, my parents bought a house with a garden in a neighborhood that consisted of single-family houses on one side of the street and public housing complexes on the other